Dosage effects of organic manure on bacterial community assemblage and phosphorus transformation profiles in greenhouse soil - Zhang, Liangliang; Niu, Junfang; Lu, Xuewei; Zhao, Ziyue; Li, Kaixuan; Wang, Fenghua; Zhang, Chaochun; Sun, Ruibo (Frontiers in Microbiology, 2023)
Manure is a potential substitute for chemical phosphate fertilizer, especially in intensive agriculture, such as greenhouse farming, but the associations between soil phosphorus (P) availability and the soil microbial community under manure application instead of chemical phosphate fertilizers are still rarely addressed. In this study, a field experiment in greenhouse farming with manure application instead of chemical phosphate fertilizers was established, including five treatments: a control with conventional fertilization and chemical phosphate fertilizer substitution treatments using manure as the sole P resource at 25% (0.25 Po), 50% (0.50 Po), 75% (0.75 Po), and 100% (1.00 Po) of the control. Except for 1.00 Po, all the treatments applied with manure harbored similar levels of available P (AP) as the control. Most of the bacterial taxa involved in P transformation were enriched in manure treatments. Treatments of 0.25 Po and 0.50 Po significantly enhanced bacterial inorganic P (Pi) dissolution capacity, while 0.25 Po decreased bacterial organic P (Po) mineralization capacity. In contrast, the 0.75 Po and 1.00 Po treatments significantly decreased the bacterial Pi dissolution capacity and increased the Po mineralization capacity. Further analysis revealed that the changes in the bacterial community were significantly correlated with soil pH, total carbon (TC), total nitrogen (TN), and AP. These results revealed the dosage effect of the impact of manure on soil P availability and microbial P transformation capacity and emphasized that an appropriate dosage of organic manure is important in practical production.